Inattention and switching costs as sources of inertia in medicare part D - Florian Heiss; Daniel McFadden; Joachim Winter; Amelie Wuppermann; Bo Zhou (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
Consumers' health plan choices are highly persistent even though optimal plans change over time. This paper separates two sources of inertia, inattention to plan choice and switching costs. We develop a panel data model with separate attention and choice stages, linked by heterogeneity in acuity, i.e., the ability and willingness to make diligent choices. Using data from Medicare Part D, we find that inattention is an important source of inertia but switching costs also play a role, particularly for low-acuity individuals. Separating the two stages and allowing for heterogeneity is crucial for counterfactual simulations of interventions that reduce inertia.
Keywords: I13; D12; J14; C25; 330; Medicare; prescription drugs; health insurance demand; dynamic discrete choice